Behavioral predictability in a lynx spider is interactively influenced by mean behavior, prey density, and an insecticide. Issue 6 (30th November 2017) - Michalko, Radek; Košulič, Ondřej; Pung, Thitiya; Vichitbandha, Patchanee
Abstract: Behavioral predictability, i.e., short-term intra-individual variability under relatively constant environmental conditions, has only recently begun to gain attention. It is unknown, however, whether predictability of individuals with distinct mean behavior changes differently as a response to ecological factors such as resource availability. Moreover, the response might be affected by anthropogenic contaminants that are ubiquitous in the environment and that can affect animals' variability in behavior. Here, we investigated the relationship between mean predatory activity and predictability in predatory activity along a prey density gradient in the lynx spider Oxyopes lineatipes . We further examined how this relationship is influenced by insecticides, azadirachtin, and a plant extract from Embelia ribes . We found that all studied variables affected the predictability. In the control and Embelia treatments, that did not differ significantly, the predictability decreased with increasing prey density in a mean behavior-specific way. Individuals with low mean predatory activity were relatively less predictable than were those with high activity from low to moderate prey densities but more predictable at high prey densities. Azadirachtin altered this pattern and the individuals with low predatory activity were less predictable than were those with high predatory activity along the whole gradient of prey density. Our results show that predictability can change along an environmental gradient depending on a mean behavior. The relative predictability of the individuals with distinct mean behavior can depend on the value of the environmental gradient. In addition, this relationship can be affected by anthropogenic contaminants such as pesticides.